Ecology of sensing - Barth, Friedrich G. 1940-; Schmid, Axel (Springer Berlin Heidelberg, 2001)
Sense organs serve as a kind of biological interface between the environment and the organism. Therefore, the relationship between sensory systems and ecology is very close and its knowledge of fundamental importance for an understanding of animal behavior. The sixteen chapters of this book exemplify the diversity of the constraints and opportunities associated with the sensation of stimuli representing different forms of energy. It stresses the events taking place in the sensory periphery where the animal is exposed to and gets in touch with its natural habitat and acquires the information needed to organize its interaction with its environment. Ecology of Sensing brings together the leading experts in the field